Knowledge, Attitude and Practice Regarding Organ Donation among Indian Dental Students - Chakradhar, K. (Int J Organ Transplant Med, 2016)
BACKGROUND: Of the overall 9.5 million deaths annually in India, nearly 100,000 are due to organ failure. To save and extend lives, organ donation and organ transplantation have become the only hope. Health care professionals (HCPs) are a key element in facilitating cadaveric organ donation process. OBJECTIVE: To assess and compare the knowledge, attitude, and practice regarding organ donation among undergraduate dental students. METHODS: A cross-sectional study was conducted among 298 undergraduate dental students of the Panineeya Institute of Dental Sciences and Hospital, Hyderabad, India. A 27-item self-administered questionnaire, which assessed the levels of knowledge (Q1–13), positive attitude (Q14–24) and practice habits (Q25–27) regarding organ donation with dichotomous scale (Yes/No). RESULTS: As compared to males, females reported better mean±SD scores in knowledge (8.22±1.51) and practice (0.91±0.8); higher mean±SD attitude scores (8.55±1.56) were reported among males (p<0.001). While second year dental students had higher scores for their knowledge (8.55±1.56) and practice (1.02±0.44) compared to other year of training, third year students showed a significant higher mean attitude score (1.73±1.17) (p=0.02). Hindus and Muslims scored significantly lower mean knowledge, attitude and practice habits compared to others (Christians, Jains and Athesists) (p<0.001). There was a positive correlation between mean knowledge, attitude, and practice habits. CONCLUSION: There are an average level of knowledge and low levels of positive attitude and practice habits among studied dental students towards organ donation and transplantation.